حُكْم التّصرف في مَال الزَكَاة بالقَرْض الحَسَن - صُندُوق الزَكَاة الجَزائِري نمَوذَجاً- - معطالله, كريمة; مونة, عمر (جامعة الوادي university of eloued, 2022)
ملخص: اهتم البحث بالكشف عن الحكم الشرعي للإقراض من مال الزكاة، فتم فيه عرض لآراء العلماء ومداركهم في المسألة؛ فكان لهم رأيان: الجواز والمنع؛ وبناءً على ما تمت دراسته، فإنّنا نخلص بأنّ القول بالمنع هو الأقرب للصواب؛ لأنّه يستند إلى نصوص شرعية، ويُحافظ على دور الزكاة في القضاء على الدُّيون لا في إنشائها، وفي كونها الطرف الضامن لعملية الإقراض، ووجود الضمان يُشجع الناس على تقديم قروض حسنة، فيكون ذلك تجفيفاً لمنابع الربا بوجود البديل الذي يُغني عن اللجوء للقُروض الربوية. فعلى مؤسسات الزكاة الأخذ برأي الـمنع مـُحافظة على أموال الزكاة، وعلى دورها الجوهري في تنظيم هذه الفريضة بجمعها من أكبر شريحة من الـمُزكين، وهذا يحتاج لتعزيز ثقة الناس، وتبني تلكم التصرفات المختلف فيها يجعلها تفقد مصداقيتها. Abstract :The research aims to reveal the legal ruling for lending from zakat money. Hence, scholars’opinions and perceptions on the issue were presented; They had two opinions: permissibility and prohibition. Based on what has been presented in this study, we conclude that the statement of prohibition is the closest to the pertinence. Indeed, it is based on legal texts, and preserves the role of zakat in eliminating debts, not in their creation, and in being the guarantor of the lending process. moreover, the presence of guarantee encourages people to provide good loans, so that drains the sources of usury with the existence of an alternative that dispenses with resorting to usurious loans; Zakat institutions should take the opinion of the ban in order to preserve the zakat funds, and their essential role in organizing this obligation by collecting them from the largest segment of the payers, and this needs to enhance people’s confidence, and adopt those different behaviors that make them lose their credibility
He Law Of Disposing Of Zakat Money With A Good Loan - The Algerian Zakat Fund As A Model
مقال
Keywords: القرض الحسن؛ الزكاة؛ الحكم؛ التصرف؛ مؤسسات الزكاة؛ صندوق الزكاة الجزائري.; Zakat; the law; disposingZakat institutions; the Algerian Zakat Fund